2016
DOI: 10.1139/cjpp-2015-0461
|View full text |Cite
|
Sign up to set email alerts
|

Effect of valsartan on cardiac senescence and apoptosis in a rat model of cardiotoxicity

Abstract: The clinical application of doxorubicin is limited by its cardiotoxicity. The present study investigated the effect of valsartan on doxorubicin-induced cardiotoxicity in rats. Rats were divided into 6 groups: control, control + valsartan (10 mg/kg, for 14 days, orally), doxorubicin-treated (2.5 mg/kg, 3 times/week for 2 weeks, intraperitoneally), valsartan then doxorubicin, valsartan + doxorubicin, and doxorubicin then valsartan. ECG, isolated heart, lipid peroxidation (thiobaribituric acid reactive substances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 53 publications
1
23
0
1
Order By: Relevance
“…Consistent with previous studies [ 39 ], our data showed that DOX administration in rats caused a significant increase in lipid peroxidation, which was manifested by pronounced elevations in MDA and was also accompanied by a notable decrease in TAC of rats’ cardiac tissue. These effects were not unexpected since previous studies had demonstrated DOX-induced depletion of antioxidant molecules including glutathione (GSH) and exhaustion of cardiac antioxidant enzymes including catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-P) due to excessive consumption by DOX-generated free radicals [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies [ 39 ], our data showed that DOX administration in rats caused a significant increase in lipid peroxidation, which was manifested by pronounced elevations in MDA and was also accompanied by a notable decrease in TAC of rats’ cardiac tissue. These effects were not unexpected since previous studies had demonstrated DOX-induced depletion of antioxidant molecules including glutathione (GSH) and exhaustion of cardiac antioxidant enzymes including catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-P) due to excessive consumption by DOX-generated free radicals [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies demonstrated detailed histological and electron microscopic data of DOX-induced myocardial changes, such as myofibrillar disarray [60], myofibrillolysis, sarcomeric disintegration [9, 61], contraction band formation [10], and cardiomyocyte hypertrophy [61, 62]. Some of these abnormalities were successfully attenuated by inhibiting the renin–angiotensin–aldosterone system [10, 15, 16]. In contrast with a conventionally scheduled therapy, we demonstrated a well-preserved ultrastructure of the myofilaments when applying a prophylactic treatment, which highlights the importance of the temporal aspects of cardioprotection in preserving myocardial ultrastructure.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical observational study demonstrated that Val could prevent the acute cardiotoxicity induced by cyclophosphamide, doxorubicin, vincristine and prednisolone, which are standard chemotherapeutic options for treatment of non-Hodgkin lymphoma ( 11 ). More recently, Sakr et al ( 12 ) investigated the effect of Val on DOX-induced cardiotoxicity in rats, and found that concurrent or post-but not pre-treatment with Val attenuated DOX-induced cardiotoxicity by inhibiting oxidative stress, apoptosis and senescence. Another study reported that Val alleviated DOX-induced cardiac dysfunction via regulation of the TGF-β signaling pathway ( 13 ).…”
Section: Introductionmentioning
confidence: 99%